Global biogeographic synthesis and priority conservation regions of the relict tree family Juglandaceae (2020)
Aim: To establish a complete database of Juglandaceae at a spatiotemporal scale and develop a phylogeographic framework with which to elucidate the distributional patterns, diversity patterns, origins, evolution, and conservation priority regions of this family. Location: Worldwide. Taxon: Walnut family (Juglandaceae). Methods: Data on the distribution of all the extant and fossil species of Juglandaceae were collected, followed by analyses of its latitudinal distribution, elevational distribution, and species and generic diversity. Furthermore, based on all genera and 87% of the species, we reconstructed phylogenetic relationships, estimated divergence times, calculated phylogenetic diversity and inferred ancestral distributions. Results: Extant Juglandaceae (10 genera and 60 species) are mainly distributed in eastern Asia and North America (principally between 20 and 40°N). Tropical Juglandaceae mainly inhabit mountainous areas higher than 1,000 m, especially in the New World. Southwest China and northern Vietnam are characterized by high species, generic and phylogenetic diversity. The United States of America has only high species diversity. The area of origin of Juglandaceae was North America and Europe in the early Eocene, and its widespread dispersal mainly occurred between 13 and 26 Ma. Main conclusions: The members of Juglandaceae inhabit areas with temperate climatic conditions. The diversification centre has shifted intercontinentally from North America and Europe to Southwest China and northern Vietnam, which are identified as conservation priority regions. The high-latitude cooling during the Oligocene followed by a long-term stable warmer climate in the early and middle Miocene drove the southward translocation of the family. © 2019 John Wiley and Sons Ltd